2011
DOI: 10.1002/cncy.20184
|View full text |Cite
|
Sign up to set email alerts
|

On‐site adequacy evaluations performed by cytotechnologists

Abstract: BACKGROUND: Practice patterns regarding on‐site assessment of the adequacy of image‐guided fine‐needle aspiration biopsies (FNABs) vary among laboratories, but in many laboratories primary responsibility rests with the cytotechnologists. On‐site evaluation provides feedback on the need for additional passes and facilitates triaging of the specimen for time‐sensitive ancillary studies. Prior studies have suggested that cytotechnologists can assess the initially obtained specimens correctly, but they are few in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 33 publications
(56 reference statements)
2
19
0
Order By: Relevance
“…The cost is justified easily on an institutional scale when the decreased rebiopsy rate and efficient use of a cytopathologist's time are considered [17], but few medical delivery systems are integrated well enough to allocate resources so holistically. As such, the practice remains the domain of large academic centers [11,12,13,14,18]. This is likely to change, given the emergence of telecytology and the growth of accountable care organizations.…”
Section: Discussionmentioning
confidence: 99%
“…The cost is justified easily on an institutional scale when the decreased rebiopsy rate and efficient use of a cytopathologist's time are considered [17], but few medical delivery systems are integrated well enough to allocate resources so holistically. As such, the practice remains the domain of large academic centers [11,12,13,14,18]. This is likely to change, given the emergence of telecytology and the growth of accountable care organizations.…”
Section: Discussionmentioning
confidence: 99%
“…The largest study of cytotechnologists as OSEA providers demonstrated highly desirable results [20] although the number of pancreas biopsies was small, and there was no comparison with the performance of cytopathologists in the same role at the same institution. In contrast, in this study we examine the accuracy of both cytotechnologists and cytopathologists in performing OSEA during EUS-guided FNA of the pancreas.…”
Section: Introductionmentioning
confidence: 99%
“…This is probably the case because in order for institutions to engage in un-reimbursed cytotechnologist-performed OSEA, they have to evaluate the cost-effectiveness on a macro-scale institutional level [12]. Large academic centers, for example, have been quick to give cytotechnologists these duties [13,14,15]. While a randomized clinical trial has yet to be performed and published, the data shown here and elsewhere [13,14,15] have shown sufficient performance of cytotechnologists for OSEA and form a sufficient basis for pursuing this level of evidence as part of the evidence needed to request the addition to the current medical services fee schedule.…”
Section: Discussionmentioning
confidence: 99%
“…Given the time constraints on practicing cytopathologists, divesting them from other clinical functions in order to perform OSEA presents a significant logistical challenge. Alternatives have been proposed including non-cytologist-performed OSEA [10,11] and cytotechnologist-performed OSEA [12,13,14,15]. Our own experience has shown that cytotechnologists perform similarly to cytopathologists in OSEA of thyroid [14] and endoscopic ultrasound (US)-guided pancreas FNA [15].…”
mentioning
confidence: 99%